Detection of salbutamol and enantioselective sensing of l/d-lysine based on a cadmium-based coordination polymer. (7th December 2022) - Jia, Yuejiao; Li, DeChao; Wu, Nan; Su, Shuai; Qie, Shaowen; Hu, Ming
Abstract : An achiral Cd II -based coordination polymer could sensitively recognize salbutamol via a turn-on effect and distinguish l /d -lysine by different fluorescence responses. Abstract : In this work, a one-dimensional zigzag chain coordination polymer, [Cd(pbca)2 ]·2C2 H5 OH n (1 ), was synthesised using the 2-(pyridin-2-yl)-1 H -benzoimidazole-5-carboxylic acid (Hpbca) ligand and transition metal salts in a water/ethanol solvent system. Compound 1 further forms a three-dimensional supramolecular structure through hydrogen-bonding interactions. The fluorescence probe properties showed that the activated solvent-free sample of compound 1 (denoted as 1a ) can be used to quantitatively identify salbutamol, and also it could distinguish l /d -lysine by different fluorescence responses, the detection limits of salbutamol and l -lysine were 1.22 × 10 −7 M and 1.44 × 10 −7 M, respectively. It was found that compound 1a had excellent anti-interference properties and recyclability for the detection of the above substances. Meanwhile, the fluorescence response mechanisms of compound 1a for different analytes were elucidated through characterization using FT-IR, PXRD, and DFT calculations and the Benesi–Hildebrand equation. This study not only provides a viable sensor for the sensitive and selective detection of salbutamol in simulated urine samples but also provides a promising strategy for achieving the fluorescence identification of chiral amino acids by using achiral coordination polymers.